Escherichia coli aggravates inflammatory response in mice oral mucositis through regulating Th17/Treg imbalance - Liu, Jia; Xia, Wenhui; Cheng, Juehua; Geng, Yanlin; Li, Weiping; Fan, Yuan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMicrobial dysbiosis links to mucosal immune dysregulation, but the specific bacterial contributions to oral mucosal inflammation remain unclear. Escherichia coli (E. coli), a pathogen well-characterized in mucosal immunity and immune regulation studies, has been observed to be enriched in chronic oral inflammatory lesions and was reported to modulate T helper 17 cells (Th17)/T regulatory cells (Treg) homeostasis. Here, we developed an oral mucositis mouse model via tongue scratch and E. coli topical application to investigate its role in Th17/Treg imbalance.MethodsThe inflammatory infiltration was evaluated by macroscopic photography and HE staining. The expression of inflammatory factors in tongue tissue and peripheral blood of mice were detected by immunohistochemical staining and enzyme-linked immunosorbent assay. The number of Th17 and Treg in mice spleen lymphocytes were evaluated with flow cytometry. Differential gene expression analysis, functional enrichment analysis and immune infiltration analysis were performed using RNA-seq data from oral lichen planus (OLP).ResultsE. coli stimulation aggravated inflammatory responses induced by scratching in lingual mucosa of mice, including increased local and systemic expression of interleukin 6 (IL6), interleukin 17 (IL17), chemokine receptor 6 (CCR6) and chemokine C-C motif ligand 20 (CCL20), increased proportions of Th17 cells and increased Th17/Treg ratio in spleen lymphocytes. Analysis of RNA-seq data from OLP revealed alterations in antimicrobial responses and inflammatory factors associated with upregulation of Th17/Treg balance.ConclusionThis study supports the role of E. coli in promoting oral mucosal inflammation and provides an experimental basis for in vivo study of OLP from the perspective of microorganisms.